2008
DOI: 10.1038/ejcn.2008.35
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectric impedance spectroscopy underestimates fat-free mass compared to dual energy X-ray absorptiometry in incurable cancer patients

Abstract: Background/Objectives: Weight loss is frequently seen in advanced cancer. Bioelectrical impedance spectroscopy (BIS) is a convenient method for estimating body composition. We examined in a prospective, comparative study if BIS could accurately estimate fat-free mass (FFM) in cancer patients compared to dual-energy X-ray absorptiometry (DXA). Subjects/Methods: The study was based on 132 consecutive incurable cancer patients with solid tumours in a University hospital outpatient clinic. Comparison of FFM from D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 27 publications
1
35
0
3
Order By: Relevance
“…Although no significant differences were found between methods, very wide limits of agreement (B10 kg) for BIS predictions were observed for all groups, which suggests the limited clinical use of BIS for patients with end-stage renal disease. Ellegård et al 49 found that BIS significantly underestimated FFM in cancer patients who had undergone large weight losses. The bias of the BIS prediction was significantly correlated with percent weight loss and biochemical indices of malnutrition and weight loss.…”
Section: Estimation Of Fluid Volumes In Health and Diseasementioning
confidence: 99%
“…Although no significant differences were found between methods, very wide limits of agreement (B10 kg) for BIS predictions were observed for all groups, which suggests the limited clinical use of BIS for patients with end-stage renal disease. Ellegård et al 49 found that BIS significantly underestimated FFM in cancer patients who had undergone large weight losses. The bias of the BIS prediction was significantly correlated with percent weight loss and biochemical indices of malnutrition and weight loss.…”
Section: Estimation Of Fluid Volumes In Health and Diseasementioning
confidence: 99%
“…In addition, this method has been reported to correlate extremely well with the evaluation of body composition by computed tomography, magnetic resonance imaging and dual energy X-ray absorptiometry (15,(20)(21)(22)50,51). The current findings indicate that regularly assessing the body composition, using the BI method, of patients with pancreatobiliary tract cancer receiving GEM-based chemotherapy is a useful adjunct index for understanding pathological conditions and for predicting the continuation of chemotherapy treatment.…”
Section: Discussionmentioning
confidence: 59%
“…14 Furthermore, it has been shown that BIS and BIA frequently underestimate body composition variables in cancer patients compared with dual-energy X-ray absorptiometry. 41 Some of these deviations can be compensated for by using adequate mathematical transformations accounting for BMI or weight of the patient but phase angle and FFM may deviate significantly between individuals. However, another small exploratory study in 24 patients with head and neck cancer compared the FFM measured via BIA and dual-energy X-ray absorptiometry over the course of radiation treatment and did not find a significant difference between the measurement methods.…”
Section: Evaluation Of Nutritional Status Using Bia Measuresmentioning
confidence: 99%